2020
DOI: 10.1109/access.2020.2983739
|View full text |Cite
|
Sign up to set email alerts
|

A Reliable Localization Algorithm Based on Grid Coding and Multi-Layer Perceptron

Abstract: The traditional RSS-based fingerprint localization algorithm needs RSS values from all access points (AP) at each reference point (RP). In the large-scale indoor environment, the increasing of the number of APs will lead to establish a large-scale fingerprint database, which occupies a lot of storage space. In this paper, we propose a new reliable localization algorithm, which firstly utilizes quantized RSS to encode the monitoring region which has been divided into grids, so as to specify the grids that the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…In [15], an extraction of fingerprint features known as the Fisher Score-Stacked Sparse Auto-Encoder (Fisher-SSAE) technique was proposed building a hybrid localization model to prevent major coordinate localization errors accredited to subregional localization errors obtaining a mean position error of 2.09 m. However, the positioning moving target was not taken into account in this study. Sun et al [16] suggested a new accurate machine learning algorithm that first uses RSSI to encode the monitoring area and then grid regions are trained using Multi-Layer Perceptron (MLP), reducing the size of the fingerprint database by more than 80% with enhanced localization accuracy. An enhanced neighboring RPs selection method for Wi-Fi-based indoor localization was suggested in [17].…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…In [15], an extraction of fingerprint features known as the Fisher Score-Stacked Sparse Auto-Encoder (Fisher-SSAE) technique was proposed building a hybrid localization model to prevent major coordinate localization errors accredited to subregional localization errors obtaining a mean position error of 2.09 m. However, the positioning moving target was not taken into account in this study. Sun et al [16] suggested a new accurate machine learning algorithm that first uses RSSI to encode the monitoring area and then grid regions are trained using Multi-Layer Perceptron (MLP), reducing the size of the fingerprint database by more than 80% with enhanced localization accuracy. An enhanced neighboring RPs selection method for Wi-Fi-based indoor localization was suggested in [17].…”
Section: Related Workmentioning
confidence: 99%
“…Methods Mean position error Li et al [11] IFCM & WkNN 2.53 m Gu et al [12] Landmark graph-based fingerprint collection method 1.5 m Abbas et al [13] Deep learning model 1.21 m Hoang et al [14] RNN 0.75 m Wang et al [15] Fisher-SSAE 2.09 m Sun et al [16] MLP 1.73 m Xue et al [17] RP selection method 2.6 m Bai et al [20] SISAE & RNN 1.60 m Ayesha et al [24] GA & EDOP 1.149 m Li et al [25] F S kNN 1.7 m Li et al [26] W kNN 0.9 m 3 Background…”
Section: Authormentioning
confidence: 99%